2010
DOI: 10.2994/057.005.0205
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Studies of the GenusPhymaturus(Iguania: Liolaemidae): Description of Four New Species

Abstract: after the study of a diverse collection of Phymaturus from three argentinian institutions and additional samples collected in the last two years we discovered several populations of uncertain taxonomic status. Based on 93 morphological characters of squamation, color pattern, gular and nuchal folds, precloacal pores, and morphometric data, we conclude that at least four of those are independent lineages which require formal description. characters related to sexual dimorphism and dichromatism as well as the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 14 publications
0
37
0
8
Order By: Relevance
“…This could be an artifact of our present knowledge, since the species diversity of Brazil is still high, but it seems that the tendency in Argentina will follow that of previous years, and more species are being discovered with more intense field sampling and detailed systematic studies. On the other side, some species have been suggested as synonyms of other species, like Phymaturus agilis, P. gynechlomus, and P. dorsimaculatus , Lobo et al 2010a, Lobo et al 2012a, and probably some species of Liolaemus can also be synonimized. The high number of lizard's species in Argentina is mainly attributed to the high number of species of the Liolaemus and Phymaturus genera.…”
Section: Discusion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be an artifact of our present knowledge, since the species diversity of Brazil is still high, but it seems that the tendency in Argentina will follow that of previous years, and more species are being discovered with more intense field sampling and detailed systematic studies. On the other side, some species have been suggested as synonyms of other species, like Phymaturus agilis, P. gynechlomus, and P. dorsimaculatus , Lobo et al 2010a, Lobo et al 2012a, and probably some species of Liolaemus can also be synonimized. The high number of lizard's species in Argentina is mainly attributed to the high number of species of the Liolaemus and Phymaturus genera.…”
Section: Discusion and Conclusionmentioning
confidence: 99%
“…(Bell, 1843). Scolaro (2010) recently redescribed the neotype of Phymaturus palluma, suggesting the "UspallataParamillos" site as type locality and rejected the proposed synonym of P. gynechlomus with P. palluma by Lobo et al (2010a).…”
Section: Phymaturus Gynechlomus Corbalán Scolaro and Debandi 2009mentioning
confidence: 99%
“…The characters for description were taken from Etheridge (1995), Lobo and Quinteros (2005), and Lobo et al (2010Lobo et al ( , 2012a. The description of colors in life is based on photographs of recently collected specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Etheridge (1995) subdivided Phymaturus into two groups-palluma and patagonicus. Based on the results of a phylogenetic analysis of morphological, skeletal and cytogenetic characters of Phymaturus, Lobo and Quinteros (2005) reported that the northern species of the P. palluma Group (that occur in northwestern San Juan, approximately north of 30 o 20' S), represent a monophyletic subgroup, which was named the Puna Clade (Lobo et al 2010). This…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation